Rectus femoris myotendinous lesion treated with PRP: a case report - Pogliacomi, Francesco; Visigalli, Alberto; Valenti, Pier Giulio; Pedrazzini, Alessio; Bernuzzi, Gino; Concari, Giorgio; Vaienti, Enrico; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of work: Musculoskeletal injuries are the most common cause of severe, chronic pain and physical disability for the majority of all sport-related injuries. Platelet-rich plasma is being used more frequently to promote healing of muscle injuries. We report a case of 39 years old non professional soccer player who came to our attention for a quadriceps muscle pain onset after kicking the ball during a match. Methods: Clinical and instrumental evaluation revealed a myotendinous junction rupture of the rectus femoris with retraction of 1.5 cm from the anterior inferior iliac spine. We decided to treat the patient with PRP ultrasound guided injections and a specific rehabilitation protocol. Results: Clinical evaluation 45 days following the end of the treatment showed the resolution of the pain and the full recovery of strength and range of motion. Muscle healing was documented by magnetic resonance imaging. Conclusions: Even if the role of PRP in muscle injury is not still clear, the result observed confirms that it could be used in the treatment of muscle lesions.